(untitled) (GESTIÓN Y TENDENCIAS, 2024)
This article examines the in-depth interview as a critical qualitative technique for obtaining valuable information in market research. It discusses its foundations as a semi-structured dialogue aimed at understanding consumers’ beliefs, motivations, and behaviors from a genuine perspective. The study sets out seven stages for its successful implementation, highlighting the laddering technique for connecting product attributes with deeply held personal values. It also proposes a thematic analysis model for turning textual data into actionable strategic insights. The paper concludes by weighing the advantages of detailed exploration against limitations such as interviewer bias and low statistical representativeness.